Taxonomy and phylogeny of the genus Steinera (Arctomiales, Arctomiaceae) in the subantarctic islands of Crozet and Kerguelen - Ertz, Damien; Poulsen, Roar S.; Charrier, Maryvonne; Søchting, Ulrik (Phytotaxa, 2017)
The lichenized genus Steinera is revised for the archipelagos of Crozet and of Kerguelen, with a high level of endemism revealed. It is shown to represent a good example of convergent evolution between two different orders. Phylogenetic analyses using nuLSU, RPB1 and mtSSU sequences show that two different species groups can be recognized: Steinera s. str. belongs to the Arctomiaceae (Arctomiales) and is characterized notably by species having pluriseptate ascospores, and a second species group belongs to the Koerberiaceae (Peltigerales) and is characterized notably by simple ascospores sometimes having a plasma-bridge. The genus Henssenia is newly described to accommodate this latter group. The type species of Steinera is shown to have been erroneously treated in the past, with Steinera molybdoplaca being the type of Steinera and “S.” glaucella belonging to the genus Henssenia. A sorediate morph is recorded for S. molybdoplaca and the results confirmed using a 4-gene phylogeny, including nuITS sequences. Some species previously described in the genera Arctomia and Massalongia from the Southern Hemisphere are shown to belong to Steinera s. str. Five new species are described: Steinera isidiata Ertz & R.S. Poulsen, S. membranacea Ertz & R.S. Poulsen, S. lebouvieri Ertz, S. pannarioides Ertz & R.S. Poulsen and Henssenia subglaucella Ertz & R.S. Poulsen along with seven new combinations: Steinera intricata (Øvstedal) Ertz, S. latispora (Øvstedal) Ertz, S. olechiana (Alstrup & Søchting) Ertz & Søchting, S. subantarctica (Øvstedal) Ertz, Henssenia glaucella (Tuck.) Ertz, R.S. Poulsen & Søchting, H. radiata (P. James & Henssen) Ertz and H. werthii (Zahlbr.) Ertz, R.S. Poulsen & Søchting. An epitype is chosen for Henssenia glaucella and a neotype for H. werthii. “Steinera” symptychia has an isolated phylogenetic position in the Koerberiaceae and might represent a distinct, new genus. World-wide identification keys to the species of Henssenia and Steinera are provided.